MEMBANGUN DESA BERSIH TERTATA MELALUI PROGRAM KKN DI DESA NGIDIHO KECAMATAN GALELA BARAT - Kastanja, Ariance Yeane; Mussy, Yohanis; Mintia, Alberth D.; Patty, Zeth (HIRONO : Jurnal Pengabdian Masyarakat, 2024)
Community Service Activities in the form of KKN which were carried out in Ngidiho Village for 2 months were aimed at providing learning experiences for students, helping the Ngidiho Village community to improve the cleanliness of the village environment and providing a new Village Blue Print for use by the village government and community. This activity involved 10 KKN students from Hein Namotemo University, Field Supervisors (DPL) and Responsible for KKN whose implementation was carried out in several stages, namely: preparatory activities, carrying out village clean-up actions, making village plans and evaluation stages. The results of the activity evaluation show that all activities designed together with the community and KKN students at the location can meet the targeted achievements, so that this activity can be said to provide benefits to the people of Ngidiho Village.